2014
DOI: 10.1002/cncr.28589
|View full text |Cite
|
Sign up to set email alerts
|

Disparities of cancer incidence in Michigan's American Indians: Spotlight on breast cancer

Abstract: Introduction In American Indians (AI), cancer is a leading cause of mortality, yet their disease burden is not fully understood due to unaddressed racial misclassification in cancer registries. This study describes cancer trends among AIs in Michigan, focusing on breast cancer, in a linked data set of Indian Health Service (IHS), tribal and state cancer registry data adjusted for misclassification. Methods AI status was based upon reported race and linkage to IHS data and tribal registries. Data with complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Consistent with the literature, our study found that African American (13,39), Hispanic white (13,40), Asian/Pacific Islander (1,3) and American Indian/Alaska Native (1,3,41,42) women had elevated risks of being diagnosed with more advanced stages of breast cancer compared to non-Hispanic white women. As reported by previous studies, African American (1,3,4345) and Hispanic white(1,3,45) patients with early stage breast cancer were also more likely to receive inappropriate primary treatment following breast cancer diagnoses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the literature, our study found that African American (13,39), Hispanic white (13,40), Asian/Pacific Islander (1,3) and American Indian/Alaska Native (1,3,41,42) women had elevated risks of being diagnosed with more advanced stages of breast cancer compared to non-Hispanic white women. As reported by previous studies, African American (1,3,4345) and Hispanic white(1,3,45) patients with early stage breast cancer were also more likely to receive inappropriate primary treatment following breast cancer diagnoses.…”
Section: Discussionsupporting
confidence: 91%
“…Beyond confirming that American Indian/Alaska Native are more likely to be diagnosed with more advanced stage breast cancer overall (1,3,41,42), we found this risk was confined primarily to triple-negative disease. According to a 2010 national survey, American Indian/Alaska Native reported the lowest breast cancer screening rate of all women aged 40 years or older, 63.9% compared to 75.4% among non-Hispanic whites (54).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The likelihood of this population to reside on rural reservations and reliance on IHS eligibility for access to care can diminish researchers’ ability to gather accurate data on the AI/AN population, especially given the relatively lower incidence of breast cancer in this group. Analyzing data for AI/AN women can be problematic in that racial and ethnic minority individuals tend to be underrepresented in cancer registries; this is often related to racial misclassification, which for the AI/AN population may be very high (Roen, Copeland, Pinagtore, Meza, & Soliman, 2014). Additionally, incidence rates for AI/AN women may be less stable than for other racial/ethnic groups, due to the limited geographic areas in which their populations occur in high enough rates to aggregate data (Wingo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…American Indians/Alaska Natives are more likely than members of other racial groups to be misclassified for race in cancer registries. 12-18 Restricting AI/AN data to IHS Contract Health Service Delivery Area (CHSDA) counties has been identified as one way to address racial misclassification; 19 however, nearly half of Michigan counties are non-CHSDA. 20…”
mentioning
confidence: 99%